2004
DOI: 10.1111/j.1365-2249.2005.02653.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitoxantrone induces cell death in peripheral blood leucocytes of multiple sclerosis patients

Abstract: Summary Mitoxantrone (MX) is a cytotoxic drug with proven clinical efficacy in active multiple sclerosis (MS). In this ex vivo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 23 publications
1
46
0
Order By: Relevance
“…These results extend recent reports that higher concentrations of mitoxantrone (as achieved soon after i.v. infusion) can mediate immune cell necrosis, whereas at lower concentrations mitoxantrone can trigger immune cell apoptosis (20,21). Together, these findings support the notion that mitoxantrone induces the preferential death of CD19 ϩ CD27 ϩ memory B cells, resulting in a relatively higher proportion of circulating CD19 ϩ CD27 Ϫ naive B cells.…”
Section: Treatment With Mitoxantrone Results In Reciprocal Modulationsupporting
confidence: 76%
See 2 more Smart Citations
“…These results extend recent reports that higher concentrations of mitoxantrone (as achieved soon after i.v. infusion) can mediate immune cell necrosis, whereas at lower concentrations mitoxantrone can trigger immune cell apoptosis (20,21). Together, these findings support the notion that mitoxantrone induces the preferential death of CD19 ϩ CD27 ϩ memory B cells, resulting in a relatively higher proportion of circulating CD19 ϩ CD27 Ϫ naive B cells.…”
Section: Treatment With Mitoxantrone Results In Reciprocal Modulationsupporting
confidence: 76%
“…Mitoxantrone, recently approved for the therapy of MS, is a relatively nonselective anti-metabolite chemotherapeutic drug thought to impact both T cell and B cell responses (20,21). We applied our ex vivo assay to B cells freshly isolated from a sequential cohort of MS patients before and during standard mitoxantrone treatment (23).…”
Section: Treatment With Mitoxantrone Results In Reciprocal Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Comparison of peripheral blood mononuclear cells obtained from MS patients, before and immediately after application of mitoxantrone, exhibited a decreased proliferation of peripheral blood mononuclear cells based on necrotic cell death, predominantly in B cells. 27 Fidler et al 21 reported a decreased secretion of the pro-inflammatory cytokines interferon-␥, tumor necrosis factor-␣ and interleukin (IL)-2. In contrast, recent ex vivo analysis of the cytokine profile of immune cells obtained from patients before and during treatment with mitoxantrone revealed a decrease of IL-10 (an anti-inflammatory cytokine) expressing monocytes and a decrease of IL-2R-␤1 expressing T cells after six months of treatment.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…They are strictly contraindicated for long term use as they are associated with a number of side effects (Merck,). Chemotherapeutics with a potential of suppressing the immune system like mitoxantrone inducing the apoptosis of lymphocytes and cyclophosphamide acting against both the T & B-cell activities, were also tried against RR and secondary progressive MS (Chan et al, 2005;Fauci et al, 1971; Multiple Sclerosis Treatments). The drugs in development for MS are Fingolimod and BG00012 that are in phase II clinical trials.…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%